Baseline characteristics of the 1149 patients recruited into the Rapid Intervention with Glyceryl trinitrate in Hypertensive stroke Trial-2 (RIGHT-2) randomized controlled trial. Issue 3 (April 2019) - Bath, Philip M; Scutt, Polly; Appleton, Jason P; Dixon, Mark; Woodhouse, Lisa J; Wardlaw, Joanna M; Sprigg, Nikola
Background: High blood pressure is common in acute stroke and associated with a worse functional outcome. Glyceryl trinitrate, a nitric oxide donor, lowers blood pressure in acute stroke and may improve outcome. Aims: Rapid Intervention with Glyceryl trinitrate in Hypertensive stroke Trial-2 (RIGHT-2) tested the feasibility of performing a UK multicenter ambulance-based stroke trial, and the safety and efficacy of glyceryl trinitrate when administered by paramedics before hospital admission. Methods: Paramedic-led ambulance-based multicenter prospective randomized single-blind blinded-endpoint parallel-group controlled trial of transdermal glyceryl trinitrate (given for four days) versus sham in patients with ultra-acute (<4 h) presumed stroke. Data are number (%), median (interquartile range) or mean (standard deviation). Results: Recruitment ran from October 2015 to 31 May 2018. A total 1149 patients were recruited from eight UK ambulance services and taken to 54 acute hospitals. Baseline characteristics include: mean age 73 (15) years; female 555 (48%); median time from stroke to randomization 70 (45, 115) min; face-arm-speech scale score 2.6 (0.5); and blood pressure 162 (25)/92 (18) mmHg. The final diagnosis was ischemic stroke 52%, hemorrhagic stroke 13%, Transient Ischemic Attack (TIA) 9%, and mimic 25%. The main trial results will be presented in quarter 4 2018. The results will also be included in updated Cochrane systematic reviews, and individual patient data meta-analyses of all relevant randomized controlled trials. Conclusion: It was feasible to perform a multicenter ambulance-based ultra-acute stroke trial in the UK and to treat with glyceryl trinitrate versus sham. The relatively unselected cohort of stroke patients is broadly representative of those admitted to hospital in the UK. Trial registration: ISRCTN26986053.